HUBUNGAN ANTARA MOTIVASI BELAJAR DARI ORANG TUA DENGAN MINAT BELAJAR MATEMATIKA PADA MASA PANDEMIK - Reni Sinta Dewi; Amran Amran (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2020)
This study aims to examine the relationship between parents 'motivation to learn and students' interest in learning. This research was conducted in June 2020 for fourth grade students of Papandayan State Elementary School, Bogor City, which consisted of 43 students. The data analysis technique used simple and regression analysis which produced a relationship model in the form of a regression equation, namely Ŷ = 6.44 + 0.626x, which means that the functional relationship is significant. The strength of the relationship between the variables serving with the correlation coefficient = 0.984 with the coefficient of determination (KD) = 0.97 indicates that 97% of interest in learning can be generated from the existence of learning motivation from parents